Analisis Kesalahan EBI Dalam Papan Merek Toko Jalan R.E. Martadinata Hingga Jalan Muradi Kota Sungai Penuh - Frans Sudirjo; Umul Khasanah; Nelvia Susmita; Mas’ud Muhammadiah; Andi Muh Akbar Saputra; Petrus Jacob Pattiasina (Journal on Education, 2023)
This study is intended to analyze Indonesian-language errors in the writing of store signage in the Sungai Penuh City area. The object of his research was the writing on the signboards of shops, billboards, and banners in the Sungai Penuh City area. Researchers chose the brand board of the store in Sungai Penuh City as the research site because in this region there were a lot of writing errors on the signboards of shops. This research was conducted using a qualitative approach with a descriptive method. This study aims to determine the form of EBI errors in the form of the use of capital letters and absorption elements contained in the writing of the store brand sign on R.E. Martadinata street to Muradi Street, Sungai Penuh City. Based on the data found in the field and the results of the analysis, it can be concluded that many errors in Indonesian language were found in the writing of store signage found along R.E. Martadinata street to Jalan Muradi, Sungai Penuh City. This is because there are still many store brands whose writing is not / does not comply with good and correct Indonesian rules. Of the 30 billboards, 3 billboards were found that experienced EBI errors in the form of capital letter usage and 27 billboards that experienced EBI errors in the form of the use of absorption words contained in billboard writing on R.E. Martadinata street to Jalan Muradi, Sungai Penuh City.